2004
DOI: 10.1002/ijc.20291
|View full text |Cite
|
Sign up to set email alerts
|

Omega‐3 fatty acids improve liver and pancreas function in postoperative cancer patients

Abstract: Key words: omega-3 fatty acid; fish oil; soybean oil; immunonutrition; inflammation; acute-phase response; parenteral nutritionEpidemiologic studies have indicated that high intake of saturated fat and/or animal fat increases the risk of colon and breast cancers. 1 Further laboratory experiments showed reduced risk of colon carcinogenesis after omega-3 PUFA supplementation. In a phase II clinical trial of patients with colonic polyps, dietary FO supplements inhibited cell proliferation. Mechanisms accounting f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
105
1
13

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(124 citation statements)
references
References 39 publications
4
105
1
13
Order By: Relevance
“…In a randomized, controlled double-blind study, Heller AR and colleagues [19,20] demonstrated that no coagulation and platelet abnor malities are evoked by fish oil supplementation as high as 0.2 g/kg per day for five postoperative days. In the present study, the change in platelet counts showed no statistical difference between the two groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a randomized, controlled double-blind study, Heller AR and colleagues [19,20] demonstrated that no coagulation and platelet abnor malities are evoked by fish oil supplementation as high as 0.2 g/kg per day for five postoperative days. In the present study, the change in platelet counts showed no statistical difference between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our results demonstrate that the serum level of γ-GT on POD+8 in the FO group was lower than that in the SO group. Heller AR et al [20] found that after a major abdominal tumor surgery, fish oil supplementation could improve liver and pancreas function. Animal experiments have demonstrated improved perfusion and fewer translocations of viable bacteria from the gut into the mesenteric lymph nodes and liver after omega-3 fatty acid infusion in rats [22,23] .…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, the anticarcinogenic properties of LC n-3 PUFA, which are mainly attributed to altered PG formation due to COX-2 inhibition, may prove beneficial in pancreatic cancer 240 . Fish oil in total parenteral nutrition improved patient recovery and indices of pancreatic and hepatic function in postoperative cancer patients 231,241 . After elective surgery for cancer, enteral nutrition supplemented with LC n-3 PUFA resulted in reduction of gastrointestinal complications and infections by 50% (ref.…”
Section: Critically Ill Patients Cancer and Other Chronic Diseasesmentioning
confidence: 99%
“…On the other hand, some investigators have demonstrated that dopamine, through the extracellular signal-regulated kinase pathway, reduced the suppressive activity and the adhesive and migratory abilities of Treg cells ( 9 ). Several studies have recently shown that n-3 PUFA, abundantly present in fi sh oils, inhibit cancer cell growth ( 10,11 ). Besides, n-3 PUFA exert immunosuppressive effects on T-cell proliferation (12)(13)(14).…”
Section: In Vitro Cell Proliferation Assaymentioning
confidence: 99%